2001
DOI: 10.1081/pfc-100103738
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Imidazolinone Herbicides With Soil Humic Acids. Experimental Results and Molecular Modeling

Abstract: Adsorption and desorption isotherms of the herbicides imazapyr, imazethapyr and imazaquin on a soil humic acid have been performed at pH 2.8 and 4.0 (below and above the pKa of the herbicides). At both pH, adsorption increased according to the lipophilic character of the molecules (imazapyr Ͻ imazethapyr ϽϽ imazaquin). The extent of adsorption was higher at pH 2.8 than at pH 4.0 because of the partial ionization of the carboxylic groups of both herbicides and humic acids at increasing pH. Desorption of imazapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
1
21
1
1
Order By: Relevance
“…However the intrinsic mechanism by which it affects cellular function still needs to be clarified. It has been demonstrated that humate has a strong affinity to bind to several compounds, such as herbicides [10] and mutagens [11,12]. The possibility exists that humate adsorbs pro-inflammatory molecules such as cytokines and complement factors.…”
Section: Discussionmentioning
confidence: 99%
“…However the intrinsic mechanism by which it affects cellular function still needs to be clarified. It has been demonstrated that humate has a strong affinity to bind to several compounds, such as herbicides [10] and mutagens [11,12]. The possibility exists that humate adsorbs pro-inflammatory molecules such as cytokines and complement factors.…”
Section: Discussionmentioning
confidence: 99%
“…They have strong affinity for mutagens (Cozzi et al 1993), pesticides (Negre et al 2001;Li et al 2003), monoaromatic and polycyclic aromatic compounds (Nanny and Maza 2001;Kollist Siigur et al 2001), heavy metals (Livens 1991;Madronova et al 2001;Hammock et al 2003;Herzig et al 2007;Zralý et al 2008), aflatoxin B 1 (Van Rensburg et al 2006) and microorganisms (Fein et al 1999). Positive effects of oxihumolite resulting in a decreased ammonia emission in the inside environment of broiler and pig housing were noted by Suchý et al (1999) and Herzig et al (2001).…”
mentioning
confidence: 85%
“…Colloidal characteristics of HA and their salts and their ability to form chelates, they can significantly modify the toxic effects of a number of xenobiotics and undesirable substances that enter the digestive tract together with feeds and water (Livens, 1991;Herzig et al, 1994). Their strong affinity to mutagens (Cozzi et al, 1993), pesticides (Negre et al, 2001;Li et al, 2003), monoaromatic and polycyclic aromatic compounds (Kollist Sügur et al, 1993;Nanny and Maza, 2001), heavy metals (Livens, 1991;Madroňová et al, 2001;Hammock et al 2003;Herzig et al, 2007), aflatoxin B1 (Van Rensburg et al, 2006) and microorganisms (Fein et al, 1999) was described. Positive effects of oxihumolite resulting in a decreased ammonia concentration in the stable environment of market broilers were obtained by Suchý et al (1999).…”
Section: Humic Acidsmentioning
confidence: 99%